Evaluating the Community’s Adaptive Capacity to Climate Change at the Household Level: Evidences from a Survey in Rang Dong Town, Nghia Hung District, Nam Dinh Province - Tuyet, Dam Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
This research used the sustainable livelihood framework developed by the Department for International Development of the United Kingdom (2001) to evaluate the community’s adaptive capacity to climate change in Rang Dong town, Nghia Hung district, Nam Dinh province. In-depth interviews were conducted with 79 households to explore their opinions and rating about symptoms and impacts of climate change related to their families’s livelihoods. The interviews also focused on the methods that the households used to respond to climate change. The research findings show that the households’ capacity to climate change is generally weak. The households’ livelihood resources there are utlised at a low level and these resources are insufficient to support them in responding to climate change. Keywords Livelihood framework, adaptive capacity, climate change, community level References [1] DFID, Sustainable Livelihood Guidance Sheets, Department for International Development, London, UK, 2001. [2] Dasgupta, S., Laplante, B., Meisner, C., Wheeler, D. & Jianping, Y., The impact of seal level rise on developing countries: A comparative analysis, World Bank, 2007. [3] MONRE, Kịch bản biến đổi khí hậu, nước biển dâng cho Việt Nam, Bộ Tài nguyên và Môi trường, 2012. [4] MONRE, Kịch bản biến đổi khí hậu, nước biển dâng cho Việt Nam, Bộ Tài nguyên và Môi trường, 2009. [5] Yusuf, A.A. & Francisco, H., Climate change vulnerability mapping for Southeast Asia, Economy and Environment Program for Southeast Asia (EEPSEA), 2009. [6] Polsky, C., Neff, R. & Yarnal, B., "Building comparable global change vulnerability assessments: The vulnerability scoping diagram", Global Environmental Change, 17 (2007) 3-4, 472-485. [7] Huyện ủy huyện Nghĩa Hưng, Báo cáo số 81, 2012. [8] Chi cục Thống kê huyện Nghĩa Hưng, Báo cáo tổng kết tình hình kinh tế huyện Nghĩa Hưng, tỉnh Nam Định, 2012. [9] Bennett, A. & Elman, C., "Qualitative research: recent developments in case study methods", Annual Review of Political Science, 9 (2006), 24. [10] Berg, B.L., Qualitative research methods for the social sciences Allyn & Bacon, Boston, 2000. [11] Dawson, C., A practical guide to research methods, Spring Hill House, Oxford, 2007, [12] Patton, M.Q., "Depth interviewing", How to use qualitative methods in evaluation SAGE publications Inc., 1987, 108-144. [13] Yin, K.R., Case study research: Design and methods, SAGE Publications, California, 2009, [14] Easterby-Smith, M., Thorpe, R. & Lowe, A., "Qualitative methods", Management research: An introduction, SAGE Publications Ltd, 2002, 85-130.